The Worldwide Expansion of Higher Education in the Twentieth Century - Schofer, Evan; Meyer, John W. (American Sociological Review, 2005)
The authors analyze the rapid worldwide expansion of higher educational enrollments over the twentieth century using pooled panel regressions. Expansion is higher in economically developed countries (in some but not all analyses) as classic theories would have it. Growth is greater where secondary enrollments are high and where state control over education is low, consistent with conflict and competition theories. Institutional theories get strong support: growth patterns are similar in all types of countries, are especially high in countries more linked to world society, and sharply accelerate in virtually all countries after 1960. The authors theorize and operationalize the institutional processes involved, which include scientization, democratization and the expansion of human rights, the rise of development planning, and the structuration of the world polity. With these changes, a new model of society became institutionalized globally-one in which schooled knowledge and personnel were seen as appropriate for a wide variety of social positions, and in which many more young people were seen as appropriate candidates for higher education. An older vision of education as contributing to a more closed society and occupational system—with associated fears of “over-education”—was replaced by an open-system picture of education as useful “human capital” for unlimited progress. The global trends are so strong that developing countries now have higher enrollment rates than European countries did only a few decades ago, and currently about one-fifth of the world cohort is now enrolled in higher education.